Silver-containing calcium phosphate materials of marine origin with antibacterial activity. Issue 8 (September 2015) - Piccirillo, C.; Pullar, R.C.; Tobaldi, D.M.; Lima Castro, P.M.; Estevez Pintado, M.M.
Abstract: Hydroxyapatite (Ca10 (PO4 )6 (OH)2 – HAp) is a common material for bone replacement in artificial implants and prostheses, due to its high biocompatibility. In this work we report about the preparation of HAp-based materials of marine origin with antibacterial properties. Bones from cod fish ( Gadhus morua ) were treated with a dilute AgNO3 solution, to obtain HAp-containing samples with silver as a minor component. The samples were characterised by XRD, FT-IR spectroscopy and SEM, indicating the presence of HAp, β–TCP and some metallic silver. The determination of unit cell parameters, however, indicated that the majority of silver is substituted in the β-TCP lattice in ionic form. The antibacterial activity of these materials was tested towards both Gram-positive and Gram-negative bacterias; results showed that the material is very effective with Gram-negative strains such as Escherichia coli (inactivation rates of 99.82% and 99.999% after 2 and 5 h, respectively) and had a smaller but still significant effect on Gram-positive MRSA (91% inactivation rate). These results show the potentials of these samples as infection-resistant bone replacement materials.